2022
DOI: 10.1037/edu0000736
|View full text |Cite
|
Sign up to set email alerts
|

Greater income inequality, lower school belonging: Multilevel and cross-temporal analyses of 65 countries.

Abstract: Students' school belonging is critical to overall functioning. Most past studies of school belonging's antecedents focused on individual-level and proximal environmental factors, neglecting broader socioecological factors such as income inequality. Hence, this study examined whether income inequality is associated with students' school belonging. We further examined whether having high socioeconomic status could buffer the harmful consequences of income inequality on school belonging. We drew on 822,230 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 134 publications
0
25
0
Order By: Relevance
“…These effects held despite controlling for country‐ and school‐level economic resources, suggesting that it is not only the absolute amount of economic resources but also the dispersion of these resources that could explain maladaptive social relationships (Due et al., 2009). Higher inequality led to lower feelings of school belonging (King et al., 2020).…”
Section: Cultural and Ecological Perspectives On Achievement Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects held despite controlling for country‐ and school‐level economic resources, suggesting that it is not only the absolute amount of economic resources but also the dispersion of these resources that could explain maladaptive social relationships (Due et al., 2009). Higher inequality led to lower feelings of school belonging (King et al., 2020).…”
Section: Cultural and Ecological Perspectives On Achievement Motivationmentioning
confidence: 99%
“…For example, researchers have found that higher levels of inequality led to lower levels of reading, math, and science scores. More interestingly, motivational factors such as intrinsic motivation also paid lower dividends in such unequal contexts (King et al., 2020). among 15‐year‐old students.…”
Section: Cultural and Ecological Perspectives On Achievement Motivationmentioning
confidence: 99%
“…However, the pernicious effects of inequality cannot be reduced only to an increase in poverty. Studies of child and adolescent health and life satisfaction (e.g., Elgar et al, 2015, 2017), educational participation (e.g., Kearney & Levine, 2016; King et al, 2022) and bullying (e.g., Contreras et al, 2015; Elgar et al, 2013) all indicate that income inequality is a unique predictor of variance in children's well‐being after controlling for family income.…”
Section: Introductionmentioning
confidence: 99%
“…By the time they reach adolescence, they have a detailed knowledge of socioeconomic differences and hierarchies within their society (Cabieses et al, 2015). It also seems likely that higher inequality increases the salience of income differences (Cheung & Lucas, 2016; King et al, 2022) and may make children more aware of their family position in the income hierarchy. In a working paper for UNICEF, Alemán‐Díaz et al (2016) concluded that the negative effects of inequality on poorer children stemmed from both the restrictions and stresses associated with living in poverty and the additional stress created by their awareness of their relative socioeconomic position which can lower their self‐esteem and self‐efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, from an evolutionary perspective, while overall unequal distributions act as an economic stressor threatening people's survival, abundant material resources in developed countries may protect people against the influence of inequality (Oishi et al, 2022), which makes it possible that inequality affects values more in developing than developed countries. Although existing research has shown some evidence for main effects of both economic development and economic inequality on values, it remains unclear whether and if so how wealth and economic inequality may interact to affect individual psychological characteristics (King et al, 2022; Ngamaba et al, 2018; Oishi & Kesebir, 2015). Therefore, we adopt an exploratory approach to studying the interactive effects of economic development and economic inequality on values (exploratory research question 1, ERQ1).…”
Section: Introductionmentioning
confidence: 99%